Corollospora mediterranea: A Novel Species Complex in the Mediterranean Sea - Anna Poli; Elena Bovio; Iolanda Perugini; Giovanna Cristina Varese; Valeria Prigione (Applied Sciences, 2021)
The genus Corollospora, typified by the arenicolous fungus Corollospora maritima, consists of twenty-five cosmopolitan species that live and reproduce exclusively in marine environments. Species of this genus are known to produce bioactive compounds and can be potentially exploited as bioremediators of oil spill contaminated beaches; hence their biotechnological importance. In this paper, nine fungal strains isolated in the Mediterranean Sea, from the seagrass Posidonia oceanica (L.) Delile, from driftwood and seawater contaminated by an oil spill, were investigated. The strains, previously identified as Corollospora sp., were examined by deep multi-loci phylogenetic and morphological analyses. Maximum-likelihood and Bayesian phylogeny based on seven genetic markers led to the introduction of a new species complex within the genus Corollospora: Corollospora mediterranea species complex (CMSC). The Mediterranean Sea, once again, proves an extraordinary reservoir of novel fungal species with a still undiscovered biotechnological potential.